Twist velocity model of single slide skill on the U-ground - Liu, X. Y.; Li, M. Y.; Zhang, S. S. (Applied Mechanics and Materials, 2012)
It is a hot research project of single slide skill on the U-ground in Winter Olympic Games. According to the force acting on the U side by snowboarder, considering Newton's second and third laws, the maximum twist formula are derived, the calculating results show that twist angle is increased up to 15% by using our model.